Social Forces Impeding Development of Science and Technology in Tanzania: The Case of Secondary School Science Education - Matogwa, Armstrong C. (Papers in Education and Development, 2023)
This study examines the relationship between natural science knowledge and development of science and technology in Tanzania. It is a response to the puzzle that, why despite decades of dissemination of modern science knowledge, Tanzania is still technologically behind? The study uses qualitative methods of data generation and accumulation by disarticulation conceptual framework to analyze and explain this puzzle. Findings suggest that, imperialist forces in forms of colonialism, neocolonialism and neoliberalism have sporadically weakened the development of science and technology. In the neoliberal era, schools disseminate eurocentric, reified and disarticulated science that limits students ' potentialities to invent and innovate relevant and articulated technologies. The study recommends on reconceptualization of natural science knowledge and dissemination of an articulated version. Keywords: articulated knowledge, disarticulation, eurocentrism, natural science,